KARDIOCHIRURGIA DOROSŁYCHConcentrations of vascular endothelial growth factor, C-reactive protein and interleukin 6 in patients qualified to surgical treatment of coronary artery disease - Krejca, Michał; Krzych, Łukasz; Wasiak, Michał; Bochenek, Andrzej; Mróz, Iwona (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Atherosclerosis is a chronic inflammatory disease involving release in such biochemical markers as C-reactive protein (CRP) and interleukin 6 (IL-6). Attention was already given to pro-atherosclerotic role of vascular endothelial growth factor (VEGF). The study aimed to assess the concentrations of VEGF, CRP and IL-6 in patients qualified to surgical treatment of coronary artery disease and to correlate the values with lipids’ concentrations. Material and Methods: In a case-control study, we investigated 38 patients (aged 65.6 ±10.0) qualified to coronary artery bypass grafting (CABG) (study group), and 37 healthy volunteers (aged 24.3 ±7.6) as a control group. The control group consisted of healthy outpatients with proper lipids’ concentrations, and negative history of pharmacological treatment or any heart disease. Results: Study group subjects had higher CRP and VEGF concentrations compared to controls (p < 0.05) with no difference in IL-6 concentrations between groups. VEGF was positively correlated with total cholesterol (R = 0.42; p = 0.03) and LDL concentrations (R = 0.48; p = 0.01), and CRP was negatively correlated with HDL level (R = –0.45; p = 0.02). In the control group CRP was also negatively correlated with HDL concentration (R = –0.88; p = 0.002). After adjustment for potential confounders, CRP was associated with total cholesterol (b = 0.64; p = 0.004), HDL (b = –1.25; p < 0.0001) and triglyceride (b = –0.25; p = 0.02) concentrations, and VEGF was dependent only on LDL level (b = 41.7; p = 0.05). Conclusions: Subjects qualified to CABG have higher CRP and VEGF concentrations compared to subjects without coronary artery disease. VEGF is positively correlated with total cholesterol and LDL concentrations, and CRP is negatively correlated with HDL and triglyceride concentrations.